7) - 5 + (e + 6) - 2 * (3e - 4) + 2e - 3 = 8
-5 + e + 6 - 6e + 8 + 2e - 3 = 8
-3e + 6 = 8
-3e = 2
e = -⅔
8) 4a - (a - 7) + 3(4 + 2a) = 5
4a - a + 7 + 12 + 6a = 5
9a + 19 = 5
9a = -14
a = 1 5/9
9) (2s - 3) * 3 - 6s + 4 * (2 + s) - 4s = -1
6s - 9 - 6s + 8 + 4s - 4s = -1
-1 = -1
10) (k + 2) - (k - 2) * 3 + 4k - 7 = 6
k + 2 - 3k + 6 + 4k - 7 = 6
2k + 1 = 6
2k = 5
k = 2,5
11) -6x + 4 + 4(x - 1) + 4x - 3(x + 1) = -2
-6x + 4 + 4x - 4 + 4x - 3x - 3 = -2
-x - 3 = -2
-x = 1
x = -1
12) 4(z + 7) + (z - 3) - 2 + z = -9
4z + 28 + z - 3 - 2 + z = -9
6z + 23 = -9
6z = -32
z = 5 ⅓